Masyarakat Adat Dan Perilaku Yang Dapat Mengancam Kerusakan Lingkungan - Noya, Ekberth Vallen (Pusat Kajian Pesisir dan Masyarakat Hukum Adat Fakultas Hukum Universitas Pattimura, 2024)
A customary law community is an arrangement of customary law associations whose members are bound by territorial and genealogical factors. Legal experts in the Dutch East Indies era gave the understanding that a territorial customary law community was a permanent and orderly community, which was bound to a certain area, both in worldly terms as a place of life and in spiritual terms as a place of worship for ancestral spirits. . Customary law is a rule of human custom in living in society. Since humans started families, they have arranged their lives and those of their family members according to their habits. So, seen from the development of human life, the emergence of law starts from the human person which continues to develop into habits and customs which become the customs of a society. Gradually, the community or community groups make this custom a custom that should apply to all members of society, so that it becomes